Analysis and evaluation of the levels of awareness and understanding of football tactics by a game board - Sánchez, R.; de la Vega-Marcos, Ricardo; Ruíz-Barquín, R.; Del Valle, S. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2012)
The following study addresses the relationship between the level of action and the level of representation of the subject, through the paper that provide the processes of understanding and awareness that occur within the individual when confronted with game situations sport demands a nonlinear, with features very open, like football. The objective we intend to analyze and evaluate the awareness and tactical understanding of children’s football player base, from the structural-functional perspective. For this, we used a board game football simulator, designed from the basic regulations governing the sport. The sample is composed of eight junior class male subjects, divided into two skill levels: high and low. Therefore, an analysis is centered on the player (throat, 2001). The items used for this analysis of tactical understanding of the players can be categorized according to the principles of tactical football game detailing Claude Bayer (1987). In turn, the contents listed in tactical items are classified in tactical aspects of individual type-offensive and defensive-, group-offensive and defensive-and collective-offensive and defensive-, following the classification proposed by Fradua (1997 ), Throat and Pinto (1997), Sanchez and Fradua (2001).